2019
DOI: 10.3389/fvets.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Caryospora-Like Coccidia Infecting Green Turtles (Chelonia mydas): An Emerging Disease With Evidence of Interoceanic Dissemination

Abstract: Protozoa morphologically consistent with Caryospora sp. are one of the few pathogens associated with episodic mass mortality events involving free-ranging sea turtles. Parasitism of green turtles (Chelonia mydas) by these coccidia and associated mortality was first reported in maricultured turtles in the Caribbean during the 1970s. Years later, epizootics affecting wild green turtles in Australia occurred in 1991 and 2014. The first clinical cases of Caryospora-like infections reported elsewhere in free-rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Furthermore, our findings provide information on captive juvenile green sea turtles, including turtle shells, feces, and water column. Most studies on turtle disease have focused on skin tumors ( 19 22 ), parasites ( 23 26 ), and bacterial infections ( 27 29 ), and there are few reports of infectious carapacial ulcers. Our study showed that the main bacterium in juvenile green sea turtle shells was Citrobacter freundii (91.44% on average).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings provide information on captive juvenile green sea turtles, including turtle shells, feces, and water column. Most studies on turtle disease have focused on skin tumors ( 19 22 ), parasites ( 23 26 ), and bacterial infections ( 27 29 ), and there are few reports of infectious carapacial ulcers. Our study showed that the main bacterium in juvenile green sea turtle shells was Citrobacter freundii (91.44% on average).…”
Section: Discussionmentioning
confidence: 99%
“…were identified in 1 case (Helke et al, 2006). In addition, Caryospora-like coccidia were associated with an epizootic of green turtles off the coast of the southeastern United States (Stacy et al, 2019), and 2 distinct coccidian genotypes were associated with mass mortalities in green turtles off the coast of southeast Queensland, Australia (Chapman et al, 2016). Unfortunately, with the 2017-2018 die-off of hicatees at BFREE, although 22 turtles in various states of postmortem change were necropsied in Belize, tissues were not found to be suitable for histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The apicomplexan coccidia, Caryospora cheloniae , was first identified as a pathogen in farmed 4–8-wk-old green turtles ( Chelonia mydas ) in the Cayman Islands, British West Indies (Leibovitz et al 1978 ) and in immature green turtles stranded on beaches in Australia (Gordon et al 1993 ). More recently, several outbreaks of caryosporosis have been reported in immature stranded green turtles in Florida, USA (Stacy et al 2019 ). Caryosporosis is associated with encephalitis, which is usually lethal (Gordon et al 1993 ; de Gouvea Pedroso et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%